RELEVANCE OF CHILD’S SCHOOL DIARY FOR IMPROVING CLASSROOM PROCESSES - Singh, Jaya (THE PRIMARY TEACHER, 2011)
In this article, the author examines various school diaries. On analysis, it is found that the school diaries mainly focused on the twin purposes. First, it provides an understanding of the objectives of learning as advocated by the school. Second, it examines the views of teachers and parents as recorded in the diary. The article has been divided into three sections. Section I examines the scope of the diary in terms of printed instructions it contains, Section II studies the communication among the child, parents and teachers and Section III presents the findings of the study and makes suggestions for enhancing the quality of interaction between teachers and students and between school and home in the process of schooling of children